Growth of mixed-halide perovskite single crystals. Issue 12 (2nd March 2018) - Wang, Wanfu; Su, Jing; Zhang, Lei; Lei, Yong; Wang, Di; Lu, Di; Bai, Yu
Abstract : The graph shows the mixed-halide crystals of CH3 NH3 PbI3− x Br x and CH3 NH3 PbBr3− y Cl y grown by the ITC method using mixed organic solvents. Abstract : In this paper, systematic halogen doping of CH3 NH3 PbI3− x Br x and CH3 NH3 PbBr3− y Cl y bulk single crystals that were grown in mixed organic solvents via the ITC (inverse temperature crystallization) method was performed. X-ray diffraction measurement results show that the lattice constants of CH3 NH3 PbI3− x Br x and CH3 NH3 PbBr3− y Cl y crystals change linearly with the x ( y ) values. For the CH3 NH3 PbI3− x Br x crystals, cubic to tetragonal phase transformation was observed where the iodine content reaches a certain level. The comparison of UV-vis-NIR absorption and PL spectra of CH3 NH3 PbI3− x Br x and CH3 NH3 PbBr3− y Cl y crystals shows that their absorption coefficients are contributed by direct and indirect bandgap transitions. Three kinds of mechanisms were involved in their radiative recombination, including direct emission, indirect emission and direct–indirect coexisting emission. The CH3 NH3 PbI3− x Br x ( x = 1.64, 2.39, 2.81, 2.9) crystals were considered to be indirect band gap materials, since their band edges can be divided into two regions by a turning point. TG analysis shows that the beginning decomposition temperature of CH3 NH3 PbI3− x Br x and CH3 NH3 PbBr3− y Cl y crystals decreases with increasing x ( y ) values. Research on CH3 NH3 PbI3− x Br x and CH3 NH3 PbBr3− y Cl y single crystals would be helpful to reveal the inherent properties of perovskite materials.